Identification of denitrifying bacteria from sediments of Rawa Jombor waters, Central Java and its trophic status - SUNARTO SUNARTO; RATNA SETYANINGSIH; ANDRI YANTI (Society for Indonesian Biodiversity, 2016)
Sunarto, Setyaningsih R, Yanti A. 2016. Identification of denitrifying bacteria from sediments of Rawa Jombor waters, Central Java and its trophic status. Biodiversitas 17: 578-584. Pooled freshwater (lentic) is susceptible to contamination. One of pollution contributors on freshwater is the agricultural sector. One of them is the inclusion of waste in the form of organic and inorganic materials. The waste will increase the nutrient in waters causing sedimentation, eutrophication and pollution. The pollution is from nitrates derived from agricultural wastes using inorganic fertilizers. An alternative solution for the prevention and tackling of it is to utilize aquatic microorganisms namely denitrifying bacteria. These bacteria can convert nitrates into nitrogen gas (N2) in the anaerobic state so that it can handle the pollution of nitrate in water. This study aimsed to identify the denitrifying bacteria isolated from aquatic sediments of Rawa Jombor and to determine trophic status of Rawa Jombor waters. Identification of denitrifying bacteria was done through the morphology and physiology testing phase and also molecular analysis of 16S rRNA gene sequence. Based on parameters of total nitrogen, phosphor and brightness referring to the criteria of the lake trophic status attached to Ministry of Environment (PerMNLH) No. 28 2009, Rawa Jombor aquatic trophic status was analyzed. The results showed that as many as 6 denitrifying bacteria were isolated from sediments in Rawa Jombor waters, Klaten. Characteristics of bacteria colonies were translucent, round in shape, Gram-negative, rod and motile shaped cells. Based on the analysis of 16S rRNA gene sequence, all of denitrifying bacteria isolates were identified as having the highest similarity to the Shewanella genus. TmD isolate was identified as Shewanella putrefaciens, while TmE, TmG and TmI isolates were identified as Shewanella genus and TmA isolates was new species. Trophic status of Rawa Jombor aquatic was hypereutrophication.